Effects of electrode tip morphology on resistance spot welding quality of DP590 dual-phase steel. Issue 9 (April 2016) - Wang, Bin; Hua, Lin; Wang, Xiaokai; Song, Yuke; Liu, Yali
Abstract Electrode pitting (EP) and electrode tip diameter enlargement (ETDE) are the two major representations of electrode wear, which lead to the change of electrode tip morphology and have significant impacts on the resistance spot welding (RSW) quality. In order to analyze the effects of electrode tip morphology on RSW quality of DP590 dual-phase steel, the RSW finite element (FE) model is developed to predict the nugget shape and size, whose reliability is verified by experimental observation. Tensile-shear tests are carried out to illustrate the failure behaviors. Three nugget shapes and two failure modes are obtained from different conditions of electrode tip morphology. The results show that EP morphologies produce incomplete fusion at the center of the workpieces' faying surface, while ETDE morphologies reduce the nugget sizes. Both obvious EP and ETDE morphologies resulted in a decline of lap shear fracture load (LSFL).